Optimal schemes for the use of anthelmintics at gastrointestinal strongylatosis of young cattle - I. A. Arkhipov; A. I. Varlamova; E. O. Kachanova (Российский паразитологический журнал, 2023)
The purpose of the research is to study the rational terms for the use of anthelmintics in case of gastrointestinal strongylatoses of young cattle in Nonchernozem zone of the Russian Federation.Materials and methods. The timing of the onset of re-isolation of nematode eggs with feces of cattle after the use of some anthelmintics was determined on 50 black-motley calves weighing 117–130 kg, spontaneously infected with gastrointestinal strongylates. The optimal schemes for the use of anthelmintics in case of gastrointestinal strongylatosis of young cattle were studied on 109 calves of the first year of grazing in the pasture period of 2010. After numbering, the animals were weighed and divided into experimental and control groups. Each group was divided into two subgroups of 15–17 heads. Animals of all groups from May 3 to October 10, 2018 were grazed together in one herd on a pasture where cattle infected with strongylates had previously grazed. Levamisole from the group of imidothiazoles, Alben from the group of benzimidazoles and Aversect-2 from the group of macrocyclic lactones were tested. The drugs were used in therapeutic doses: levamisole at a dose of 7.5 mg/kg by AS intramuscularly, Alben at a dose of 7.5 mg/kg with concentrated feed, and Aversect-2 at a dose of 0.2 mg/kg subcutaneously once. Levamisole was administered to the animals of the first group on the 6th, 10th and 14th weeks of grazing, and to the animals of the second group - on the 6th and 10th weeks of grazing. Alben was used on young cattle of the third group on the 6th, 11th and 16th weeks, and on the animals of the fourth group - on the 6th and 11th weeks of grazing. Aversect-2 was administered to cattle of the fifth group at the 6th, 13th and 20th weeks of grazing, and to the animals of the sixth group – at the 6th and 13th weeks. Animals of the 7th group did not receive the drug and served as control. Fecal samples were taken from animals of all groups on a monthly basis and investigated by a quantitative method in order to detect eggs of gastrointestinal strongylate. The results obtained were statistically processed using the computer program Microsoft Excel.Results and discussion. Tests of drugs for gastrointestinal strongylatoses of young cattle showed different persistence of anthelmintic action. After deworming the animals, single eggs of strongylate in their faeces were again detected 4 weeks after the administration of Levamisole, 5 weeks after the administration of Alben, and 7 weeks after the administration of Aversect-2. The most rational scheme for deworming young cattle with gastrointestinal strongylatoses is the use of Aversect-2 on the 6th and 19th weeks of grazing.